Implementation Gap of Social Forestry Policy: The Case of HKm Beringin Jaya and HTR Hajran - Budi; Hariadi Kartodihardjo; Bramasto Nugroho; Rina Mardiana (Institut Pertanian Bogor (IPB University), 2021)
The current social forestry policy is considered to accelerate the issuance of social forestry licences, but after the licence is obtained, various difficulties and obstacles are still experienced by licence holder community to achieve the objective of social forestry policy. For this reason, this study questions who is actually stakeholder or party stipulated in social forestry regulation to carry out social forestry and facilitate community to overcome the difficulties and obstacles they experienced. This study aims to analyze the implementation gap of social forestry policy towards those stipulated in social forestry regulation compared with their implementation in the field. This research was conducted at HKm Beringin Jaya and HTR Hajran. The results show that three groups of actors are stipulated in social forestry regulation, namely community with their rights and obligations, central and regional governments with their authorities and related stakeholders to support the implementation of social forestry. In two research locations, implementation gap of social forestry policy toward three groups of actors occurred in the field. The rights that can be obtained and the obligations that must be fulfilled by licence holder communities are mostly facilitated by non-governmental organizations and are influenced by the networking capacity of the community. The authority of the central and local governments to facilitate the community is not functioning adequately at the field level due to the separate political system and authority between the central and regional governments. The involvement of other related stakeholders is considered low because of their interests that must be accommodated and requiring the capacity of the community to access stakeholders.